FROM READINESS TO PRACTICE: EXPLORING GENAI AS AN ACADEMIC COUNSELING TOOL AMONG VOCATIONAL EFL TEACHERS - Putu Febry Valentina Griadhi; Made Hery Santosa; Anak Agung Gede Yudha Paramartha (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The rapid development of Generative Artificial Intelligence (GenAI) technology has brought significant changes to instructional practices and academic services in vocational education settings. This study aims to explore the functions of Generative Artificial Intelligence (GenAI) utilized by English teachers in vocational schools in supporting instructional practices and academic counseling, particularly professional practices that go beyond the readiness indicators outlined in the Readiness for Artificial Intelligence Application Scale (RAIS). This study employed a mixed-method sequential explanatory design, using a RAIS-based questionnaire for quantitative data collection and semi-structured interviews for qualitative data collection. The quantitative data were analyzed descriptively to determine teachers’ readiness levels, while the qualitative data were examined through thematic analysis to gain deeper insights into the use of GenAI in professional practice. The results indicate that teachers are categorized as “ready” for GenAI utilization, reflecting an adequate level of competence to integrate GenAI into practical, pedagogical, and ethical aspects of English language teaching. Furthermore, the thematic findings reveal that GenAI functions not only as an instructional support tool but also as an academic support tool, serving as a reflective partner, decision-making aid, assessment design facilitator, and learning data management tool. These findings highlight the evolving role of GenAI in supporting teachers’ reflective practices, pedagogical decision-making, and professional development. This study suggests the importance of practice-oriented training and the development of more comprehensive technology readiness frameworks that incorporate reflective and data-informed teaching practices. ABSTRAK Perkembangan pesat teknologi Generative Artificial Intelligence (GenAI) telah membawa perubahan signifikan dalam praktik pembelajaran dan layanan akademik di lingkungan pendidikan vokasi. Penelitian ini bertujuan untuk mengeksplorasi fungsi penggunaan Generative Artificial Intelligence (GenAI) oleh guru bahasa Inggris di sekolah vokasi dalam mendukung praktik pembelajaran dan konseling akademik, khususnya praktik profesional yang melampaui indikator kesiapan yang tercantum dalam Readiness for Artificial Intelligence Application Scale (RAIS). Penelitian ini menggunakan desain mixed-method dengan pendekatan sequential explanatory, dengan kuesioner berbasis RAIS sebagai instrumen pengumpulan data kuantitatif dan wawancara semi-terstruktur sebagai instrumen pengumpulan data kualitatif. Data kuantitatif dianalisis secara deskriptif untuk menentukan tingkat kesiapan guru, sedangkan data kualitatif dianalisis menggunakan analisis tematik untuk memperoleh pemahaman yang lebih mendalam mengenai penggunaan GenAI dalam praktik profesional. Hasil penelitian menunjukkan bahwa guru termasuk dalam kategori “siap” dalam penggunaan GenAI, yang mencerminkan tingkat kompetensi yang memadai untuk mengintegrasikan GenAI ke dalam aspek praktis, pedagogis, dan etis dalam pembelajaran bahasa Inggris. Selain itu, temuan tematik mengungkapkan bahwa GenAI tidak hanya berfungsi sebagai alat pendukung pembelajaran, tetapi juga sebagai alat pendukung akademik, yang berperan sebagai mitra reflektif, pendukung pengambilan keputusan, fasilitator perancangan asesmen, serta alat pengelolaan data pembelajaran. Temuan ini menegaskan peran GenAI yang semakin berkembang dalam mendukung praktik reflektif guru, pengambilan keputusan pedagogis, serta pengembangan profesional. Penelitian ini merekomendasikan pentingnya pelatihan yang berorientasi pada praktik serta pengembangan kerangka kesiapan teknologi yang lebih komprehensif, yang mencakup praktik pembelajaran reflektif dan berbasis data.